FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS MUARA PANAS KABUPATEN SOLOK TAHUN 2024 - Artika Ardella; Yuliza Birman; Yuni Handayani Gusmira; Mashdarul Ma’arif (Yayasan Nusantara Hasana Berdikari, 2024)
Background: Stunting is a big problem that affects children's cognitive and motor development, increasing the risk of infection, non-communicable diseases, low learning achievement to decreased productivity. In Indonesia, stunting is caused by a lack of nutritional intake and health status. Objective: Determine the factors related to the incidence of stunting in toddlers at the Muara Panas Health Center, Solok Regency in 2024. Method: The type of research is observational analytic and the research design is cross-sectional. The accessible population in this study were stunted toddlers who came to health services (posyandu) in the Muara Panas Health Center Working Area as many as 171 samples with incidental sampling techniques. Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using the chi-square test, data processing using computerized SPSS program version IBM 25.0. Results: Factors related to the occurrence of stunting are infection history (diarrhea; p=0.018; ISPA p=0.026), basic immunization (p=0.041), MP-ASI (p=0,015), maternal education level (p=0,044), family socioeconomic status (p=0,046) and Factors that are not related to stunting are BBLR (p=0,451), history of UTI infection (p=0.098), TB (p=0,291), pertussis (p= 0,192), exclusive breastfeeding history (p= 0,965), mother's age when pregnant (p= 0.131) and parity (p= 0.118). Conclusion: There is a relationship between the history of infection; diarrhea, ARI, basic immunization, complementary feeding, mother's education and family socio-economic status with the incidence of stunting. There is no relationship between birth weight, UTI, TB, Pertussis infections and parity with the incidence of stunting.